Gaps between International Tourists’ Attitudes and Behaviours towards Japanese Heritage Tourism and Government Policymakers’ Views - Opportunities for Tourism Innovation Post COVID-19 - Nguyen, Quynh Hoa; Kazem, Vafadari (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 2, 2021)
Around the world, people travel to explore natural beauty, different cultures and social traditions. Much of this involves heritage tourism and this has become an important motivation for international travelers and contributes huge economic benefits to many countries. Besides, it can also bring positive impacts to the society, culture, and environment conservation of the country involved. The Japan Tourism National Promotion Basic Law (2006) states that culture and heritage are “the most important components of Japan tourism” and that Japan will emphasize its abilities to attract more international travelers and support conservation of cultural heritage [1]. However, as a result of the COVID-19 pandemic, Japanese tourism has been damaged significantly and is forecasted to take a long time to recover. The local government shows its concerns about how to reduce the pandemic impacts on the society and economy and encourage international visitors to return. The “new normal” situation requires an insight of the changes in international tourists’ attitudes, traveling behavior and motivations. The experience of Japan could provide a model which other countries in the Asia and Pacific area might study. The research was conducted through in-depth interviews with Japanese government tourism policymakers and a quantitative survey of 211 responses from 43 countries and territories which was conducted from July 2019 to June 2020. From the findings, some recommendations for Japanese tourism innovation are proposed.